Assessment of DNA Binding to Human Rad51 Protein by using Quartz Crystal Microbalance and Atomic Force Microscopy: Effects of ADP and BRC4‐28 Peptide Inhibitor. Issue 17 (11th September 2014) - Esnault, Charles; Renodon‐Cornière, Axelle; Takahashi, Masayuki; Casse, Nathalie; Delorme, Nicolas; Louarn, Guy; Fleury, Fabrice; Pilard, Jean‐François; Chénais, Benoît
Abstract The interaction of human Rad51 protein (HsRad51) with single‐stranded deoxyribonucleic acid (ssDNA) was investigated by using quartz crystal microbalance (QCM) monitoring and atomic force microscopy (AFM) visualization. Gold surfaces for QCM and AFM were modified by electrografting of the in situ generated aryldiazonium salt from the sulfanilic acid to obtain the organic layer Au–ArSO3H. The Au–ArSO3H layer was activated by using a solution of PCl5 in CH2Cl2 to give a Au–ArSO2Cl layer. The modified surface was then used to immobilize long ssDNA molecules. The results obtained showed that the presence of adenosine diphosphate promotes the protein autoassociation rather than nucleation around DNA. In addition, when the BRC4‐28 peptide inhibitor was used, both QCM and AFM confirmed the inhibitory effect of BRC4‐28 toward HsRad51 autoassociation. Altogether these results show the suitability of this modified surface to investigate the kinetics and structure of DNA–protein interactions and for the screening of inhibitors.